Correlation analysis of serum IGF-1 and IL-6 and urinary albumin/creatinine ratio in patients with type 2 diabetic kidney disease - Liu, Guan-Wen; Zeng, Jiao-E; Li, Lan-Fang (Frontiers in Endocrinology, 2022)
Objectives: Diabetic kidney disease (DKD) is one of the most common chronic complications in diabetic patients, and there are major limitations in its pathological diagnosis. This study's objectives were to examine the changes in serum insulin-like growth factor-1 (IGF-1) and interleukin-6 (IL-6) levels in DKD patients with various urinary albumin/creatinine ratio (ACR) and to evaluate the utility of these two biological markers in the clinical diagnosis of the condition. Methods: We chose 80 type 2 diabetic patients as the experimental group and 20 healthy normal participants as the control group. The experimental group was split into three groups based on the ACR range: diabetes without nephropathy group (ACR < 30mg/g), microalbuminuric group (30< ACR < 300mg/g), and macroalbuminuric group (ACR>300 mg/g). The levels of serum IL-6 and IGF-1 were assessed in each trial participant. Results: Serum IGF-1 was higher in the experimental group than in the control group (P<0.01), and serum IL-6 levels were also higher than in the control group (P<0.001). In DKD patients, serum levels of IL-6 and IGF-1 tended to rise when ACR levels rose. By Pearson correlation analysis, serum IGF-1 and IL-6 were positively correlated with ACR (r = 0.765 and r = 0.651, all p<0.001) and negatively correlated with eGFR (r = -0.389 and r = -0.364, all p<0.01). Additionally, the receiver operating characteristic (ROC) characteristic curve showed that the area under the curve (AUC) values for serum IGF-1 and IL-6 were 0.9056 and 0.7850, respectively, while the AUR value for both combined was 0.9367. Conclusion: Serum IGF-1 and IL-6 levels can be used to diagnose DKD, and the combined analysis of these two indicators can improve the sensitivity and specificity of the disease diagnosis.